Reactivation of normal faults as high-angle reverse faults due to low frictional strength: Experimental data from the Moonlight Fault Zone, New Zealand. (December 2017) - Smith, S.A.F.; Tesei, T.; Scott, J.M.; Collettini, C.
Abstract: Large normal faults are frequently reactivated as high-angle reverse faults during basin inversion. Elevated fluid pressure is commonly invoked to explain high-angle reverse slip. Analogue and numerical modeling have demonstrated that frictional weakening may also promote high-angle reverse slip, but there are currently no frictional strength measurements available for fault rocks collected from large high-angle reverse faults. To test the hypothesis that frictional weakening could facilitate high-angle reverse slip, we performed single- and double-direct friction experiments on fault rocks collected from the Moonlight Fault Zone in New Zealand, a basin-bounding normal fault zone that was reactivated as a high-angle reverse fault (present-day dip angle 60° –75° ). The fault core is exposed in quartzofeldspathic schists exhumed from c. 4–8 km depth and contains a <20 m thick sequence of breccias, cataclasites and foliated cataclasites that are enriched in chlorite and muscovite. Friction experiments on water-saturated, intact samples of foliated cataclasite at room temperature and normal stresses up to 75 MPa yielded friction coefficients of 0.19<μ < 0.25. On the assumption of horizontal maximum compressive stress, reactivation analysis indicates that a friction coefficient of <0.25 will permit slip on high-angle reverse faults at hydrostatic (or even sub-hydrostatic) fluid pressures. Since foliated and phyllosilicate-rich fault rocks are common in large reactivated fault zones at basement depths, long-term frictional weakening is likely to act in concert with episodic build-ups of fluid pressure to promote high-angle reverse slip during basin inversion. Highlights: Friction measurements on fault rocks from basin-scale high-angle reverse fault. Phyllosilicate-rich foliated cataclasites from fault core have 0.19 < μ < 0.25 Reactivation of high-angle reverse faults due to low friction at hydrostatic fluid pressures.